Acute Respiratory Failure Complicating Advanced Liver Disease - Karcz, Marcin; Bankey, Bridget; Schwaiberger, David; Lachmann, Burkhard; Papadakos, Peter J. (Seminars in Respiratory and Critical Care Medicine, 2012)
Advanced liver disease is associated with hypoxemia and respiratory failure by various mechanisms. Patients with cirrhosis are especially prone to episodes of decompensation requiring intensive care unit admission and management. Such patients may already be in acute liver failure or have decompensated due to a concurrent illness such as spontaneous bacterial peritonitis, sepsis, encephalopathy, varices, or hepatorenal syndrome. Acute respiratory distress syndrome is one of the main reasons for intensive care unit admission and mortality. Overall, critically ill cirrhotic patients frequently progress to multiorgan failure requiring mechanical ventilation. Caring for such patients is therefore understandably complex and extremely challenging. Patients with end-stage liver disease are especially at risk for developing acute respiratory failure and hypoxemia secondary to hepatopulmonary syndrome, portopulmonary hypertension, and hepatic hydrothorax. They should therefore be screened for these conditions because failure to recognize and adequately treat these serious complications of cirrhosis may have devastating consequences. This article is based on a review of the current literature on how to approach and manage acute respiratory failure in advanced liver disease, which is important to intensivists, anesthesiologists, and physicians as a whole.
Keywords: respiratory failure; cirrhosis; acute respiratory distress syndrome; hepatopulmonary syndrome; portopulmonary hypertension; hepatic hydrothorax